Aplikasi Sistem Tanda Tangan Digital Berbasis Web Dengan Qr Code - Fenty Kurnia Oktorina (Politeknik Kampar, 2023)
Kampar Polytechnic is a vocational education institution specializing in the oil palm plantation sector. Currently, the administrative system at the institution still relies on manual signatures in the document approval process. This traditional approach is time-consuming, requires additional manpower, and carries a risk of signature forgery, which can affect the authenticity and security of important documents. In response to these issues, this research aims to develop a web-based digital signature application utilizing QR Code technology using the Laravel framework. This application is designed to streamline the document signing process, enhancing both efficiency and security. By integrating QR Codes as digital signatures, the system allows for easy document verification, ensuring the authenticity and integrity of signed documents. The development of the system employs the Unified Modeling Language (UML) method, which is used to structure and visualize the system’s architecture and workflow. The application will enable the generation of digital signatures in the form of QR Codes, which can be easily scanned and verified using a mobile device or other compatible technology.